Economic evaluation of process utility: Elucidating preferences for a non-invasive procedure to treat restenosis - Maria V. Aviles-Blanco (Health Economics Review, 2021)
Background: In health economic evaluation, utility associated with a health state is outcome-oriented and usually measured using the QALY methodology. Even though there is consistent evidence of utility not only being derived from outcomes but also from procedures, process utility has not been fully integrated in QALY calculations. The aim of this paper is twofold: first, to provide evidence of process utility associated with an alternative treatment to angioplasty, and second, to estimate a monetary value of such process utility using the willingness to pay (WTP) approach. Methods: A total of 1514 people were polled on their WTP to avoid angioplasty to have a drug-eluting stent (DES) implanted. WTP is estimated with a contingent valuation (CV) survey. Individuals are also asked if they would be WTP for a non-invasive procedure with similar results being achieved. WTP responses were analyzed using a double bounded (DB) logit model. Results: Most of the participants showed positive preferences for avoiding angioplasty, with an estimated mean WTP of exteuro5692.87. Using QALY gains for avoiding angioplasty, varying from 0.0035 to 0.08 QALYs, our WTP estimate imply monetary values per QALY that range from exteuro71,160.87 to exteuro1,626,534.28. Discussion: A WTP of exteuro5692.87 to avoid angioplasty imply a monetary value per QALY that greatly exceed the cost per QALY thresholds established in different countries to consider health programs as beneficial to society. Our results reflect how different methodologies for HTA may lead to different conclusions. From the ICER perspective, the cost that would make the treatment with pills option cost-effective, using a threshold of exteuro40,000/QALY, would be exteuro224. However, a cost-benefit approach could support health programs even with a higher cost. Conclusion: WTP methodology captures outcome and process factors related to angioplasty as our WTP estimations are non-significantly different for the costs of angioplasty. WTP approach must be considered as a genuine alternative to QALY approaches to value process utility.
Keywords: H41; H51; I11; I18; I31; 330; Process utility; Willingness to pay; QALY; Angioplasty